Influence of Green Consumer Behavior with Stimulus Organism Response (SOR) Model Analysis in Indonesian Coffeeshops - Zemafi, Okindy Dheawara; Haryono, Tulus (Universitas Muhammadiyah Surakarta, 2024)
This research investigates the impact of green marketing stimulus factors on purchasing decisions for Starbucks Indonesia products, focusing on the mediating effect of perceived value. By the SOR conceptual model, 104 respondents participated in the questionnaire survey and then the data was processed using SmartPLS SEM. This research shows that the mediating of perceived value is the most important to ensure customers' sustainable orientation towards environmentally friendly products. These findings show (a) green brand image and environmental awareness have a positive effect on perceived value; (b) there is no influence of green product price on perceived value; (c) green product price has a positive effect on purchasing decisions and there is no mediating effect of perceived value; and (d) perceived value mediates green brand image and environmental impact on purchasing decisions for Starbucks Indonesia products. This research has significant implications for understanding the market for environmentally friendly products and for companies to develop new strategies in marketing their products. This study also encourages policy makers to pay attention to the importance of environmental management and the commitment to sustainability required of entrepreneurs.